2012
DOI: 10.1007/s11103-012-9986-y
|View full text |Cite
|
Sign up to set email alerts
|

Trichome-specific expression of the amorpha-4,11-diene 12-hydroxylase (cyp71av1) gene, encoding a key enzyme of artemisinin biosynthesis in Artemisia annua, as reported by a promoter-GUS fusion

Abstract: Artemisinin derivatives are effective anti-malarial drugs. In order to design transgenic plants of Artemisia annua with enhanced biosynthesis of artemisinin, we are studying the promoters of genes encoding enzymes involved in artemisinin biosynthesis. A 1,151 bp promoter region of the cyp71av1 gene, encoding amorpha-4,11-diene 12-hydroxylase, was cloned. Alignment of the cloned promoter and other cyp71av1 promoter sequences indicated that the cyp71av1 promoter may be different in different A. annua varieties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 52 publications
1
52
0
Order By: Relevance
“…In addition, the glandular trichomes have been proposed to be the primary site for artemisinin biosynthesis and storage in the plant (Duke et al, 1994;Van Nieuwerburgh et al, 2006;Olsson et al, 2009;Wang et al, 2013). In our comparative transcriptome analysis, transcripts corresponding to putative or known monoterpenoid, diterpenoid, and (most) sesquiterpenoid biosynthesis genes were overrepresented in the glandular trichomes, as opposed to the triterpenoid transcripts, which were abundant in the filamentous trichomes (Soetaert et al, 2013).…”
Section: Terpenoid Biosynthesis Is Differentially Regulated In Trichomentioning
confidence: 70%
“…In addition, the glandular trichomes have been proposed to be the primary site for artemisinin biosynthesis and storage in the plant (Duke et al, 1994;Van Nieuwerburgh et al, 2006;Olsson et al, 2009;Wang et al, 2013). In our comparative transcriptome analysis, transcripts corresponding to putative or known monoterpenoid, diterpenoid, and (most) sesquiterpenoid biosynthesis genes were overrepresented in the glandular trichomes, as opposed to the triterpenoid transcripts, which were abundant in the filamentous trichomes (Soetaert et al, 2013).…”
Section: Terpenoid Biosynthesis Is Differentially Regulated In Trichomentioning
confidence: 70%
“…ADS is the first committed enzyme involved in artemisinin biosynthesis, which catalyzed the cyclization of farnesyl diphosphate to form amorpha-4,11-diene, the unique cyclic precursor for artemisinin (Picaud et al 2005). The ADS gene was specifically expressed in glandular trichomes which were the location of artemisinin biosynthesis in A. annua (Wang et al 2013b). A lot of publications reported that the expression level of ADS was much higher in leaf than that in root, because root did not have glandular trichomes (Olofsson et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Methyl jasmonate (MeJA) can greatly up-regulate the expression levels of ADS (Wang et al 2013a) and CYP71AV1 (Wang et al 2013b) and as a result, the content of artemisinin is consequently increased (Wang et al 2010). DBR2 expression level was not up-regulated by MeJA treatment when the UBQ gene was been used as the reference gene (Caretto et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to trichome-specific EST resources, numerous glandular trichome-specific gene promoters have been reported in the literature for a variety of plants, including (but not restricted to) Antirrhinum majus, A. annua, C. sativus, H. lupulus, Mentha spp., N. tabacum, S. lycopersicum, and S. habrochaites (Okada and Ito, 2001;Wang et al, 2002Wang et al, , 2011Wang et al, , 2013Gutiérrez-Alcalá et al, 2005;Liu et al, 2006;Jaffé et al, 2007;Kim et al, 2008;Shangguan et al, 2008;Ennajdaoui et al, 2010;Choi et al, 2012;Sallaud et al, 2012;Spyropoulou et al, 2014;Kortbeek et al, 2016;Laterre et al, 2017;Vining et al, 2017;for review, see Tissier, 2012b). It is worth noting that most of these trichome-specific promoters are active in mature glandular trichomes (mostly in glandular cells at the tip of the trichome).…”
Section: A Detailed Understanding Of Glandular Trichome Initiation Anmentioning
confidence: 99%